The Influence of Personal Selling and Promotion on Increasing Sales Through Brand Image in MSMEs Medan Food Court - Fahrezi, Alam; Tanjung, Ahmad Albar (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2024)
The aim of this research is to analyze the influence of personal selling and promotions with brand image moderating variables on increasing sales at Medan Foodcourt MSMEs . The population in this research was 46 MSMEs, taking illustrations using a saturated sampling method with a total of 46 illustrations. This research used SEM PLS analysis procedures tested using software smart PLS. The results of this research show that personal selling has a positive influence and has a big impact on brand image. The promotion has a positive and significant influence on Brand Image. Personal selling has a positive and significant influence on increasing sales. The promotion has a positive and significant influence on increasing sales. Brand Image has a positive and significant influence on Increased Sales. Personal selling through Brand Image has a positive and insignificant effect on increasing sales. Promotion through Brand Image has a positive and significant influence on increasing sales. The implications of this research suggest that Foodcourt MSMEs must focus on developing personal selling and promotional strategies that can improve brand image to achieve long-term sales growth